Association Between Breast Cancer Recurrence and Immunosuppression in Rheumatoid Arthritis and Inflammatory Bowel Disease: A Cohort Study. Issue 10 (28th September 2016) - Mamtani, Ronac; Clark, Amy S.; Scott, Frank I.; Brensinger, Colleen M.; Boursi, Ben; Chen, Lang; Xie, Fenglong; Yun, Huifeng; Osterman, Mark T.; Curtis, Jeffrey R.; Lewis, James D.
Abstract : Objective: Breast cancer recurrence may be promoted by immunosuppression due to decreased immune surveillance. The aim of this study was to examine the rates of breast cancer recurrence in patients with immune‐mediated disease and treated breast cancer who received therapy with methotrexate, thiopurines, or anti–tumor necrosis factor (anti‐TNF). Methods: Three retrospective cohort studies within Medicare (2000–2012) included women with rheumatoid arthritis (RA) or inflammatory bowel disease (IBD) who underwent surgery for primary breast cancer. Recurrent or second primary breast cancers occurring more than 365 days after the initial surgery were identified. Separate Cox regression models were used to examine the risk of cancer recurrence in patients treated with methotrexate, thiopurines, or anti‐TNF agents after surgery, each compared with no use. Analyses were matched for type of breast surgery and receipt and type of adjuvant therapy. Results: Across all medication groups, 107 women experienced breast cancer recurrence during 5, 196 person‐years. The incidence rates were 20.3 and 19.6 per 1, 000 person‐years in methotrexate users and nonusers, respectively, 32.3 and 17.6 in thiopurine users and nonusers, respectively, and 22.3 and 19.5 in anti‐TNF users and nonusers, respectively. There was no significantly increased risk of breast cancer recurrence with use of methotrexate (adjusted hazard ratio [HR] 1.07, 95% confidence interval [95% CI] 0.67–1.69), anti‐TNF therapy (HR 1.13, 95% CI 0.65–1.97), or thiopurines (HR 2.10, 95% CI 0.62–7.14). Conclusion: The risk of breast cancer recurrence in patients who received methotrexate, thiopurine, or anti‐TNF therapy was not statistically significantly increased, although we cannot rule out a 2‐fold or greater increased risk in those treated with thiopurines. These data provide reassurance to clinicians choosing to start methotrexate or anti‐TNF therapy in RA or IBD patients with treated breast cancer.